Role of the Coast Guard in the Maritime Security of India - Prabhakaran Paleri; PALERI (Prabhakaran) (New Delhi Knowledge World, 2004)
Book Summary of Role Of The Coast Guard In The Maritime Security Of India The coastguards have the capability to elevate the maritime standing of a littoral state in today's world, and also, to build international goodwill by cooperative engagement in humaritarian activities, and international law and treaty obligations.
Keywords: Military Science; Indian Navy; National Security